Study Of Physicochemical Characteristic Of Opium Effluent In Govt. Opium And Alkloid Factory Ghazipur (U.P.) - D.G. KOLHATKAR; L.P. SHINDE; J.C.BHAGURE; NIRMAL KUMAR SAHU (International Journal of Pharma and Bio Sciences, 2012)
The present study has been undertaken to investigate the physicochemical methods of analysis of opium effluent from opium and alkaloid factory work, Ghazipur, with the help of Effluent treatment Plant (ETP). Different parameters including PH, TH, CaH, Cl, COD, BOD, DO, TDS, Mg, Ca etc. are determined. The systematic study was carried out to determine the quality of untreated & treated effluent.